Pengaruh Penyuluhan Tentang Sayur dan Buah Melalui Media Video Animasi dan Media Realia Terhadap Pengetahuan dan Sikap pada Siswa di SD Negeri Cakat Raya Kabupaten Tulang Bawang Tahun 2024 - Wahyuni, Putri Eka; Nurhartanto, Adhi; Adyas, Atikah (Journal of Education Technology Information Social Sciences and Health, 2025)
In Lampung Province from 2013 to 2018 those aged 10 years who consumed less than 5 servings of fruits and vegetables per day increased. Based on data from Cakat Raya Elementary School, Tulang Bawang Regency,many children's nutritional problems were found. The purpose of this study was the effect of counseling on vegetables and fruits through animated video media and realia media on nowledge andattitudes in students at Cakat Raya Elementary School, TulangBawang Regency in 2024. This type of research is quantitative with a Quasi Experimental design with a Post-Test Only Control Group Design. Quasi Experimental. This research was conducted on July 15-19, 2024 in the Menggala Health Center Area. The population in this study was Cakat Raya Public Elementary School with 40 students. While the sample in this study was the entire population, namely 40 students consisting of an experimental group of 20 students and a control group of 20 students. This sampling used the total population. The data analysis used was univariate and bivariate analysis. The bivariate analysis used is dependent sample with paired samples statistics test. There is an influence of vegetables and fruits through animated video media and realia media on knowledge and attitudes in students at Cakat Raya Elementary School, Tulang Bawang Regency in 2024. Teachers and health center officers collaborate when they will provide routine counseling to schools in improving the knowledge and attitudes of elementary school students, especially about eating fruits and vegetables because realia media is more effective, students are more enthusiastic and the material is easy for students to understand by playing guessing the taste game.